Cloud Adoption Factors in a Specific Business Area: Challenging the Findings of Organisation-Wide Cloud Computing Research - Polyviou, Ariana; Pramatari, Katerina; Pouloudi, Nancy (My University, 2016)
Existing literature investigates cloud adoption factors and their impact on the decision to adopt cloud services in organizations. These studies consider the decision to adopt cloud services as a horizontal organization-wide decision. In this paper we argue that most of cloud decisions in practice do not regard cloud adoption horizontally across the organization. Rather, they consider cloud adoption with respect to the particular business area in which the cloud service will be introduced. These are the types of decisions we investigate in this paper. Drawing on the cloud adoption literature and Diffusion of Innovation and Organizational Capability theories, we formulate our research model involving factors related to cloud’s relative advantage and to organizational innovativeness. Our findings show that cloud’s cost-reduction and remote access benefits tradeoff security concerns as the context of cloud adoption becomes specific and demonstrate the relevance of personnel innovativeness in cloud adoption decisions.